Never stop learning stay relevant, reinvent yourself, and thrive - Bradley R. Staats (Boston, Massachusetts Harvard Business Review Press, 2018)
We now live in a learning economy, says Brad Staats, and while learning has always been important, the returns on lifetime learning are greater than ever. Our primary focus must be on our ability to learn. We must strive to develop new skills to create more value--or be left behind. As Jeff Immelt, Chairman and former CEO of GE, has noted, "You never hire somebody, no matter what the job you're hiring for, for what they know. You're hiring them for how fast you think they can learn." In Never Stop Learning, Staats outlines the framework that will help you become more effective as a lifelong learner. The steps include: Valuing failure Focusing on process, not outcome, and on questions, not answers Making time for reflection Learning to be true to yourself by playing to your strengths Pairing specialization with variety Treating others as learning partners Replete with the most recent research from behavioral science about how we learn as well as engaging stories that show how real learning happens, Never Stop Learning will become the operating manual for your brain in this new environment.-- Provided by publisher
Includes bibliographical references and index.
Keywords: Learning